Bayesian approaches for modelling complex metabolic pathways - Thomas, Duncan (Henry Stewart Talks, 2004)
Case study: asthma, Multiple environmental agents, Polygenic factors, Standard approaches: contingency tables and logistic regression methods, Latest approaches: Bayesian model averaging and pharmacokinetic modelling, Case study: colorectal cancer, Taking account of prior knowledge, The potential for application to other pathways, Biological and statistical limitations
Archived at 2021/02/25